Education Sciences Theories of “Society and Education and Individuality” - Ngoc Hung, Le (VNU Journal of Science: Education Research, 2020)
This paper discusses the need of developing the Education Science into Education Sciences of “Society & Education & Individuality” and the integration of education sciences theories into Research & Development as well as teacher training in Vietnam. The paper uses the methodology of literature review and scoping study of the articles published in the 2019 Vietnam Journal of Education and international publications on theories in education sciences. The study results indicate that though educational theories including Montessori’s education, Bloom’s taxonomy and theory of experiential learning have been widely studied and applied in teaching, the level of their application is still far from enough. Therefore, a systematic approach is needed to address theoretical problems in intensive research & development to contribute to the development of the education sciences theories of “Society & Education & Individuality” and the quality of teacher training.